Does School Functioning Matter in Patients of Child and Adolescent Mental Health Services? - Stødle, Einar S; Jozefiak, Thomas (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology, 2013)
Objective: General population studies have demonstrated that good school functioning protects children and adolescents against mental health problems. However, no such studies of clinical populations have been conducted. Therefore, we explored the association between school functioning and mental health in patients referred to child and adolescent mental health services (CAMHS). We also examined whether good school functioning and general social competence at referral predicted better mental health outcomes after six months of outpatient treatment. Method: Of 345 patients, aged 8–15.5 years, referred as outpatients to CAMHS in a Norwegian county, 192 were eligible for a six-month follow-up study. Parents filled out the Child Behavior Checklist (CBCL) for 120 of these children and teachers completed the Teachers’ Report Form (TRF) for 122 children. Results: Teacher-reported adaptive functioning (r = –0.65) and academic skills (r = –0.42), and parent-reported social competence (r = –0.35) and school competence (r = –0.27) were significantly (p < 0.01) negatively associated with total emotional and behavioral problems at baseline. Parent-reported school competence and the total level of emotional and behavioral problems at referral significantly (p < 0.05) predicted the total level of emotional and behavioral problems six months after referral. Conclusion: Both teacher- and parent-reported school functioning were associated with mental health in CAMHS patients. Only parent-reported school competence predicted total levels of emotional and behavioral problems six months after referral. Therapists, teachers, and parents should cooperate closely when planning and conducting child and adolescent psychiatric treatments, and school should be considered an important area for intervention.